PENGARUH STRATEGI PEER TUTORING UNTUK MENINGKATKAN MAHARAH KALAM SISWA KELAS XI MA MIFTAHUL ULUM PUNTIR-PURWOSARI - maulidiyah, lutfi lailatul (Universitas Muhammadiyah Mataram, 2024)
Learning Arabic in Class XI MA Miftahul Ulum Puntir-Purwosari especially in speaking Arabic even though using text in the form of kalam has not succeeded in achieving the expected goals, this can be seen from the value of student learning outcomes which are still below the minimum completeness criteria. Based on the problems faced, the right solution to be applied in learning is a strategy that can stimulate students to speak Arabic. Based on the above, the researcher is interested in taking research with the title